Copper-cysteamine nanoparticles encapsulating fluorocoumarin silicon(IV) phthalocyanines: synthesis, characterization, and photophysical properties. Issue 22 (17th December 2019) - Chen, Kuizhi; Li, Xia; Yu, Xinxin; Zhang, Tiantian; Ye, Qiuhao; Xiao, Wenling; Chen, Limin; Huang, Baoquan; Peng, Yiru
Abstract: Three nanohybrid materials (FCSiPc@PEG-Cu-Cy ) using poly (ethylene glycol) copper-cysteamine (PEG-Cu-Cy ) nanoparticles as a carrier to load three fluorocoumarin silicon(IV) phthalocyanines (FCSiPcs ) were prepared. The morphologies of these nanohybrids were characterized by transmission electron microscopy (TEM). The interactions between PEG-Cu-Cy nanoparticles and three FCSiPcs were studied by UV/Vis and fluorescence spectroscopic methods. The photophysical and photochemical properties of these FCSiPcs were influenced by PEG-Cu-Cy nanoparticles and exhibited substituents dependent of phthalocyanines in nanohybrids. The fluorescence resonance energy transfer (FRET) occurred from FCSiPcs (donors) to PEG-Cu-Cy nanoparticles (acceptors). These nanohybrids may be potential photosensitizers for photodynamic therapy. Graphical Abstract: